Influence of Self-Esteem on Fear of Intimacy Among Emerging Adults Who Have Experienced Gaslighting in Dating Relationships - Utami, Nabila Putri; Kuswartanti, Dyah Rachman; Karunia, Anindita (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2026)
Early adulthood is a crucial period in an individual's psychosocial development, where the ability to build intimate relationships is crucial. However, negative experiences in relationships, such as gaslighting, can impact an individual's psychological aspects, particularly self-esteem and fear of intimacy. Gaslighting is a manipulative form of psychological violence that can damage the victim's self-perception, lower self-esteem, and then cause anxiety about closer relationships in the future. This study aims to determine the effect of self-esteem on fear of intimacy in early adults who have experienced gaslighting in dating relationships. This study used a quantitative approach with a simple linear regression analysis technique. Respondents numbered 150 people who were early adults who had experienced gaslighting in dating relationships. The instruments used were the Self-Liking Self-Competence Scale Revised (SLCS-R) to measure self-esteem and the Fear of Intimacy Scale (FIS) to measure fear of intimacy. The results showed a significant negative effect between self-esteem and fear of intimacy, with a significance value of 0.000 (p < 0.05). The coefficient of determination of 0.238 indicates that self-esteem contributes 23.8% to fear of intimacy, with the remainder influenced by other factors. The higher an individual's self-esteem, the lower their likelihood of experiencing fear of intimacy. This finding confirms that gaslighting can undermine self-esteem and ultimately make it difficult for victims to form healthy emotional attachments in the future.